Reading between the lines: Uncovering asymmetry in the central bank loss function - Markus Haavio; Joni Heikkinen; Pirkka Jalasjoki; Juha Kilponen; Maritta Paloviita; Ilona Vänni (Bank of Finland, 2024)
We depart from the common reaction function-based approach used to infer central bank preferences. Instead, we extract the tone from the textual information in the central bank communication using both a lexicon-based approach and a language model. We combine the tone with real-time information available to the monetary policy decision-maker and directly estimate the loss function. We find strong and robust evidence of asymmetry in the case of the European Central Bank during 1999-2021: the slope of the loss function was roughly three times steeper when inflation exceeded the target compared to when it was below the target. This represents a significant departure from the quadratic and symmetric monetary policy loss function typically applied in macro models.
urn:nbn:fi-fe2024061250888
Keywords: E31; E52; E58; 330; central bank communication; textual analysis; language models; asymmetric loss function; optimal monetary policy